2012
DOI: 10.1002/hep.25874
|View full text |Cite
|
Sign up to set email alerts
|

Background progenitor activation is associated with recurrence after hepatectomy of combined hepatocellular-cholangiocarcinoma

Abstract: Hepatic progenitor cells (HPC) play important roles in both liver regeneration and carcinogenesis. Combined hepatocellular‐cholangiocarcinoma (CHC), a malignant primary liver tumor with poor prognosis, is thought to be of HPC origin. However, the prognostic significance of this etiology is not well defined. Therefore, we retrospectively investigated the relationship of HPC‐related pathological features and long‐term outcome in patients with CHC in our department. In a cohort of 80 patients identified between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 49 publications
9
63
2
Order By: Relevance
“…Our analyses showed that men were more commonly affected than women (66%), and patients were older than 60 years at the time of diagnosis (mean age at diagnosis = 62.7 years). Data regarding hepatitis virus infections, background liver status, and biomarkers such as alpha‐fetoprotein were not captured in the SEER database before 2004 and, consequently, were not included in the present analysis; they have been analyzed in the literature with contrasting results …”
Section: Discussionmentioning
confidence: 99%
“…Our analyses showed that men were more commonly affected than women (66%), and patients were older than 60 years at the time of diagnosis (mean age at diagnosis = 62.7 years). Data regarding hepatitis virus infections, background liver status, and biomarkers such as alpha‐fetoprotein were not captured in the SEER database before 2004 and, consequently, were not included in the present analysis; they have been analyzed in the literature with contrasting results …”
Section: Discussionmentioning
confidence: 99%
“…Non-tumoral ductular reaction and its proliferative index, which signifies HPC activation, were independent prognostic factors for overall and disease-free survival in CHCC-CC patients after resection [27]. In addition, soluble NCAM in patient sera was shown to be associated with poor prognosis [28].…”
Section: The Prognostic Significance Of the Hpc Signature In Hccmentioning
confidence: 98%
“…2 During chronic liver injury, the normally quiescent resident hepatic HPCs are activated and expanded from the periportal to the pericentral zone of the liver, producing reactive ductules in humans. 4,5 Reactive ductules or ductular reactions (DRs) refer to an increased number of ductules (the finest ramifications of the biliary tree), represent a regenerative response of the liver, and, thus, are a source of hepatocellular restoration during its damage or senescence. The contribution of HPCs to parenchymal restoration during liver injury is directly proportional to diminishing hepatocyte replicative potential and increasing senescence.…”
Section: Q5mentioning
confidence: 99%